The Effect of Manalagi Apple Peel Addition on the Quality of Celery Herbal Tea - Sinaga, Hotnida; Siregar, Putri Aminah; Yusraini, Era; Naibaho, Charolyne Antonia (Indonesian Journal of Agricultural Research, 2023)
Herbal tea is a refreshing drink made from dried leaves, flowers, seeds, fruit, wood, and other plants that have health benefits. The purpose of this study was to determine the ratio effect of celery with manalagi apple peel and drying time, to produce the best celery herbal tea. This study was designed using a factorial completely randomized design with 2 factors: the ratio of celery with apple peel [100:0; 75:25; 50:50; 25:75; 0:100] and drying time [2, 3, 4 hours] at 50 oC. The parameters analysed were moisture content, vitamin C content, total phenol, color, and organoleptic values (aroma, and general acceptance). The parameter observed for the best quality samples was antioxidant content. The results showed that the ratio of celery with manalagi apple peel had a highly significant effect on color oHue, aroma, and general acceptance of organoleptic. The drying time of teas had a highly significant effect on vitamin C content. The interaction of the ratio had a significant effect on the color value (L) and a highly significant effect on total phenol. The results showed that the first and the second factors had a highly significant effect on moisture content, total phenol, and color value (L). The choice of drying method can influence the final quality of the tea, making it important to select the appropriate technique.